Surgical Placement of Permanent Pacemaker Following Temporary Trasvenous Pacemaker in a Child with Congenital Heart Block and Moderate Size PDA: A Case Report - Hoque, Kazi Zahidul; Chowdhury, Masumul Gani; Munsi, Abu Sayeed; Rima, Rezoana; Hussain, Manzoor (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2016; VOL 40 (2) :124-128